2022
DOI: 10.3390/md20050312
|View full text |Cite
|
Sign up to set email alerts
|

Monkfish Peptides Mitigate High Fat Diet-Induced Hepatic Steatosis in Mice

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a hepatic metabolic syndrome usually accompanied by fatty degeneration and functional impairment. The aim of the study was to determine whether monkfish peptides (LPs) could ameliorate high-fat diet (HFD)-induced NAFLD and its underlying mechanisms. NAFLD was induced in mice by giving them an HFD for eight weeks, after which LPs were administered in various dosages. In comparison to the HFD control group: body weight in the LP-treated groups decreased by 23–28%; tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Presently, BPs have been produced from monkfish muscle and its processing by-products and showed significant bioactivities. For example, peptides fraction (MW < 1 kDa) from monkfish muscle could improve the antioxidant capacity of the liver to alleviate non-alcoholic fatty liver disease (NAFLD) progression mainly through modulating the intestinal flora and AMPK and Nrf2 pathways [ 42 , 43 , 44 ]. APs prepared from monkfish muscle hydrolysate, including EWPAQ, FLHRP, LMGQW, EDIVCW, MEPVW and YWDAW, could concentration-dependently scavenge free radicals and control lipid peroxidation [ 18 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, BPs have been produced from monkfish muscle and its processing by-products and showed significant bioactivities. For example, peptides fraction (MW < 1 kDa) from monkfish muscle could improve the antioxidant capacity of the liver to alleviate non-alcoholic fatty liver disease (NAFLD) progression mainly through modulating the intestinal flora and AMPK and Nrf2 pathways [ 42 , 43 , 44 ]. APs prepared from monkfish muscle hydrolysate, including EWPAQ, FLHRP, LMGQW, EDIVCW, MEPVW and YWDAW, could concentration-dependently scavenge free radicals and control lipid peroxidation [ 18 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skin gelatin peptides of Pacific cod could reduce and repair ultraviolet (UV)-radiated skin injuries by enhancing the activity of antioxidant enzymes and holding back the levels of nuclear factor kappa-light chain enhancer of B cells (NF-κB) and pro-inflammatory cytokines [ 28 ]. Ye et al reported that BPs from monkfish muscle could mitigate high fat diet-induced hepatic steatosis in mice through up-regulating the content of phospho-AMP-activated protein kinase (p-AMPK), which further activate the nuclear factor erythroid-2-related factor 2 (Nrf2) pathway to increase the levels of heme oxygenase-1 (HO-1) and nicotinamide quinone oxidoreductase 1 (NQO1) [ 29 ]. Pentapeptide of LCGEC from tuna roe could activate the Nrf2 pathway to decrease the apoptosis of HaCaT cells induced by UV-B radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive peptides containing 2–20 amino acids can exert various physiological effects, such as immunoregulation, antioxidant, antibacterial, antitumor, and hepato-protective impact ( 10 12 ). These peptides have been gaining increasing attention recently due to their bioactivity, high safety and bioavailability, and diverse physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hu et al ( 11 ) prepared antioxidant peptides from the protein hydrolysate of monkfish muscle, while Tian et al ( 17 ) optimized the extraction factors of antioxidant peptides from monkfish muscle, and investigated their role in H 2 O 2 -induced lesion. Ye et al ( 12 ) investigated the amelioration effect of monkfish peptides toward high fat diet-induced hepatic steatosis in mice. However, there is no report on the preparation of immunomodulatory peptides from monkfish.…”
Section: Introductionmentioning
confidence: 99%